Criminogenic Risk, Criminogenic Need, Collective Efficacy, and Juvenile Delinquency - Gearhart, Michael C. (Criminal justice and behavior, 2020)
Juvenile delinquency is influenced by reciprocal relationships between micro-level and macro-level factors. The risk, need, and responsivity (RNR) model, and collective efficacy theory are two commonly used frameworks in juvenile justice research. This study builds on previous research by testing indicators of both the RNR model and collective efficacy theory as predictors of self-reported juvenile delinquency utilizing data from the Fragile Families and Child Wellbeing Study. Taken as a whole, our findings suggest that individual-level factors are strong predictors of self-reported juvenile delinquency, whereas the relationship between collective efficacy and juvenile delinquency is limited. This finding emphasizes the importance of addressing individual needs when implementing community-level interventions aimed at preventing delinquency. Failure to do so may result in merely displacing juvenile delinquency as opposed to helping youth desist from delinquent behaviors.